Pengaruh konformitas positif terhadap kompetensi sosio-emosional yang dimediasi oleh self-efficacy pada santri remaja - Rita, Rita; Iswinarti, Iswinarti; Siti Suminarti Fasikhah (Psychological Journal: Science and Practice, 2024)
Socio-emotional competence in adolescence is needed in socio-emotional development where individuals are able to manage emotions and interact with others and develop healthy relationships. Positive conformity behavior is used as a cognitive strategy to adjust to peer groups so that deviant behavior can be avoided. In order for positive conformity to develop properly, self-efficacy is needed as a mediator to increase socio-emotional competence. The purpose of this study was to examine self-efficacy as a mediator between positive conformity and socio-emotional competence. This research method uses a quantitative approach using population quotas. The subjects in this study were all 197 students of SMP YPUI Darul Ulum Banda Aceh City. The instruments used were the Delaware Social Emotional Competence Scale-Student (DSECS-S), the Peer Conformity Disposition Scale (PCDS), and the General Self Efficacy Scale (GSES). Data analysis was performed using the Process Macro Analysis Hayes mediation analysis technique. The results of the study show that there is a significant effect of positive conformity on socio-emotional competence. With the role of self-efficacy as a mediator, positive conformity can indirectly increase the socio-emotional competence of young students at Islamic boarding schools.